A constructive analysis of the use of validity instrument in zakat research - Ismail, Nor Hanani (2019)
This aim of this paper is twofold. The first is to analyse scholars’ views on daeel (evidence) pertaining to zakat (alms-giving), while the second aim is to summarize the validity instrument used in zakat research. Validity is fundamental and important in any research. It determines whether a research could be accepted as meaningful and accurate or not. One of the principles that is used to ensure that validity is attainable is through the use of measurement from the same source. Since zakat is an Islamic asset, the validity concept that is considered acceptable to be used in the zakat research must derived from wahy or divine revelation. This is vital to ensure that there is truth and accuracy in establishing validity in the research. Numerous daleel on zakat show that the Rabbani elements such as piety of Good and purification of sins often emerge in the many discussions pertaining to zakat. The question is how do these elements be discussed in terms of validity in zakat research. How do we construct validity instrument in zakat research? This paper seeks to answer both questions through textual analysis that is conducted on several previous literature. Interviews and personal communication with four zakat experts also provide data for the analysis. Three validity indicators were formulated based on the scholars’ opinions of the daleel pertaining to zakat. The paper also recommends the use of validity instrument that has been amplified based on the experts’ viewpoints.